Compromising electromagnetic radiation - challenges, threats and protection - Markagić, Milorad S. (Vojnotehnički glasnik / Military Technical Courier, 2016)
The aim of this paper is to open up problems regarding parasitic radiation, both inductive and conductive one, originating from devices for data transmission, processing, generation and data protection as well as from their  assemblies. All devices that are used today, both in everyday use at home and in communication between individuals or institutions, contain, other than useful electromagnetic radiation, a part of useless, but also inevitable signals that are outside the control of manufacturers. Devices used for encrypting information are particularly vulnerable to this phenomenon, because every form of protection is meaningless if any part of useful information is accessible, and one of the most important segments of reaching them is monitoring parasitic radiation.
Keywords: radiation; eavesdropping; security of information